Generalised Demodicosis In A Hypothyroid Dog And Its Successful Therapeutic Management - Maharana, B.R.; Joseph, Joice P.; Thakre, B.J.; Patel, J.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Canine demodicosis is a common non-contagious parasitic dermatosis frequently encountered in veterinary practice. This disease is most commonly caused by Demodex canis ; however, other species, such as, Demodex injai (a large bodied mite) and Demodex cornei (a short bodied mite), may also be involved (Tater and Patterson, 2008). It can be of generalized or localized form. Generalised demodicosis is one of the most frustrating skin diseases, one will ever treat. Number of mite is kept low by dog’s immune system (Singh et al., 2011). Once the immune system is affected, it causes multiplication of the organisms and causes excessive and recurring lesions in the body of dog. Correction of underlying reason is necessary for therapeutic management of demodicosis.